Hubungan Peranan Orang Tua dengan Prestasi Belajar Siswa Kelas 4, 5, dan 6 di MI Darul Mubarok - Widiyanti, Diya Sri; Yuniarti, Irma (LP3M STITNU AL HIKMAH MOJOKERTO, 2023)
This research aims to find out whether there is a relationship between the role of parents and student learning achievement at MI Darul Mubarok. The research design used was descriptive qualitative. Data collection in this research used observation instruments, interviews, questionnaires and documentation. The subjects in the research were high class students (grades 4, 5, and 6), teachers (homeroom teachers for grades 4, 5, and 6), and the school principal. This research was carried out at MI Darul Mubarok which is located in Mojorejo Village, Kemlagi District, Mojokerto Regency.